2010
DOI: 10.1002/tie.20321
|View full text |Cite
|
Sign up to set email alerts
|

How location and ethnicity affect ethnic entrepreneurs in three Canadian cities

Abstract: Few studies on the entrepreneurial contributions of immigrant and/or ethnic entrepreneurs have been carried out in Canada. This article presents results from a cross‐Canadian project. Data were collected from 718 entrepreneurs in three cities. Analysis of the socio‐demographic profile suggests that ethnic entrepreneurs pursue different paths of integration. Firm characteristics suggest that similar support programs are needed for ethnic firms as for all small firms. Also, our analysis suggests that there is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
1
19
2
Order By: Relevance
“…Therefore, the decision to set up a business is based on informal information and trust in their countrymen. These findings are consistent with those obtained through other studies found in literature, which point out that immigrants trust their countrymen when seeking information related to jobs, legal issues, or about black market operations (Basu, 1998;Brenner, Menzies, Dionne, & Filion, 2010); therefore social ties are an important factor regarding the information acquired by immigrants in the host country.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the decision to set up a business is based on informal information and trust in their countrymen. These findings are consistent with those obtained through other studies found in literature, which point out that immigrants trust their countrymen when seeking information related to jobs, legal issues, or about black market operations (Basu, 1998;Brenner, Menzies, Dionne, & Filion, 2010); therefore social ties are an important factor regarding the information acquired by immigrants in the host country.…”
Section: Discussionsupporting
confidence: 92%
“…Ethnic businesses are different from those managed by native entrepreneurs not only because of the nature of the products and services supplied but also because of the characteristics of the resources that entrepreneurs utilize (Portes and Zhou 1992;Brenner et al 2010). Often, the survival or success of an ethnic firm is related to its ability to access the resources made available exclusively by the community of origin (Bonacich, 1993;Rath 2000;Rueda-Armengot and Peris-Ortiz 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…Previous research has highlighted that immigrant entrepreneurs of different ethnicities utilized personal and social capital quite differently in building their businesses. For example Brenner, Menzies, Dionne, and Filion (2010) found that the level of integration in the host country culture, and the desire to involve business contacts from country of origin differed across ethnic groups. Such differences increase the need for representative, cross-sectional studies when comparing IE to NE.…”
Section: Immigrant Ethnic and Transnational Entrepreneurshipmentioning
confidence: 99%
“…The establishment of a founding team could be seen as a way to smooth the development of their headquarters in the adoptive country. Brenner, Menzies, Dionne and Filion (2010) found that one of the greatest challenged faced by ethnic entrepreneurs is raising funds and they use their social capital in their ethnic networks to garner capital for their business through family and friends. Hence it would make sense to see more entrepreneurial teams in IE firms.…”
Section: Capitalising Teamsmentioning
confidence: 99%